The Economic Freedom and its Constitutional Protection in Chile and Spanish America: Special Reference to the case of Peru - Navarro Beltrán, Enrique (2019)
In the present article, a review of economic freedom and its protection in Chile and Latin America is carried out, making a special reference to the Peruvian case. At the same time, the author analyzes the constitutional regulation that regulates the business activity of the State.